Ring‐Opening 1, 3‐Aminochalcogenation of Donor–Acceptor Cyclopropanes: A Three‐Component Approach. Issue 50 (7th August 2019) - Augustin, André U.; Jones, Peter G.; Werz, Daniel B.
Abstract: A 1, 3‐aminothiolation was realized by reacting 2‐substituted cyclopropane 1, 1‐dicarboxylates with sulfonamides and N ‐(arylthio)succinimides. Under Sn(OTf)2 catalysis the transformation proceeded smoothly to the corresponding ring‐opened products bearing the sulfonamide in the 1‐position next to the donor and the arylthio residue in the 3‐position next to the acceptor. The procedure was extended to the corresponding selenium analogues by employing N ‐(phenylseleno)succinimides as an electrophilic selenium source. Abstract : 1+1+1 : Donor–acceptor cyclopropanes undergo a ring‐opening reaction with sulfonamides and N ‐(arylthio)succinimides in the presence of catalytic amounts of Sn(OTf)2 . A wide variety of the open‐chain structures have been obtained with high functional‐group tolerance. The transformation was extended to the corresponding selenium analogues (see scheme).